ANALISIS PENDAPATAN PEDAGANG DI PASAR SEDANA MERTA KECAMATAN KUTA UTARA KABUPATEN BADUNG DITINJAU DARI FAKTOR INTERNAL - NI MADE TAMAN AYUK (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this study was to determine the effect of internal factors on the income of traders at Sedana Merta Market, North Kuta District, Badung Regency. The internal factors to be examined are capital, labor and working hours. The research was conducted at Sedana Merta Market, North Kuta District, Badung Regency, where the object of research were traders at Sedana Merta Market. The number of samples is 76 respondents. The method used in this study is a census technique. Data collection was carried out using questionnaires, observation and documentation. The data analysis techniques used to solve the problems in this study are: 1) Classical Assumption Test which includes: Normality Test, Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test, 2) Hypothesis Testing using Multiple Linear Regression Analysis Techniques.Based on the results of the analysis, it was found that with a confidence level of 95 percent, all independent variables had an effect either simultaneously or partially on the dependent variable. This means that internal factors consisting of capital, labor and working hours affect the income of traders at Sedana Merta Market either simultaneously or partially. When viewed from the coefficient of determination, only 93.7 percent of the variation in capital, labor and working hours can explain the variation in the income of Sedana Merta Market Traders, North Kuta District, Badung Regency. This is because there are still many other factors that affect traders' income both internally and externally which are not discussed in this study.